One of ten billion earths : how we learn about our planet's past and future from distant exoplanets - Schrijver, Karel (Oxford University Press, 2018)
This book is an exploration of our Solar System and of distant planetary systems. The author explains what has recently been learned about exoplanets and their habitability, how this is done, and what it means for the search for life.